The Effectiveness Of A Guidance Program Using Self-Regulation Techniques In Reducing Social Isolation Among Widowed Women - Researcher Shihab Kazem Jawad, Supervising Professor: Prof. Dr. Mansour Sodani, Mansour Sodani, Prof.Dr. Abdul Kazem Neissi (Migration Letters, 2024)
This study examines the effectiveness of a self-regulation-focused mentoring program in reducing social isolation among widowed women. The research explores the psychological challenges faced by widows, such as social isolation, grief, and identity loss, which can lead to psychological issues. The primary objectives are to evaluate the impact of self-regulation on social isolation and to introduce a support program aimed at alleviating this common issue among widowed women. The study's significance is underscored by the urgent need to support widows, who often face societal pressures and traditions that worsen their isolation. Additionally, the study aims to influence social work and psychological counseling professionals, as well as policymakers. This study employs an experimental research design with a pretest-posttest control group approach to sample widows from the Basra Governorate in Iraq. The research instrument is a social isolation scale validated through expert evaluation and statistical analysis. Results from post-test and follow-up evaluations show that the self-regulation program significantly reduces social isolation among widowed women.[1] The study concludes that the guidance program is effective in mitigating the vulnerability of widowed women to social isolation. The research recommends extending the counseling program to other groups experiencing social isolation and investigating the relationship between social isolation and life satisfaction among widowed women. To enhance the well-being of widowed women, the study emphasizes the importance of addressing social isolation and proposes the guidance program as a viable intervention.